Uncovering the risky riding behaviors among young motorcyclist in urban areas - Siti Zun Nurain, Mohd Ali; Intan Suhana, Mohd Razelan (2022)
In Malaysia, more than 50% of road traffic crashes involve motorcyclists, with motorcyclists being the main contributor to the road crashes. Thus, the traffic safety of motorcyclists is critical and must be given priority. Road traffic crashes showed a significant increase every year in Malaysia according to Department of Road Transport statistics. Numerous researches on the relationship between risky riding behaviours and traffic accidents has been identified, however, research focuses on young motorcyclists risky riding behaviours in urban areas were somewhat limited. To demonstrate that risky riding behaviours played a significant role in the number of motorcycle crashes among motorcyclists, a motorcycle-riding-behaviour questionnaire was distributed to groups of young motorcyclists in several schools and higher education institutions to assess their level of understanding and perception of risky riding behaviour. Two primary analyses, namely frequency and percentage, rosstabulation and test of independence (chi-squared), were adopted to assess their level of understanding on motorcyclists risky riding behaviours and its correlation to crashes. Findings have proven that failing to keep proper side to side movement with another vehicle and riding while tailgating with another vehicle at an unsafe distance were highly contributed to the motorcycle crashes among the secondary school students. A greater comprehension of motorcyclists' risky riding behaviour based on their self-reported behaviour and beliefs can influence motorcyclists to make positive changes in their riding style. Hence, this result will be beneficial for enforcement bodies to strategise their effort in curbing the crash issues involving riders.